Synergism each Isolates of Thermophilic Bacteria SSA2, SSA3, SSA4, and SSAS6 in Xylanase Production - Shafa Thalita Azzahra Azzahra (Jurnal Serambi Biologi, 2023)
Enzymes are proteins that act as catalysts to speed up chemical reactions by lowering the activation energy. Enzymes and microorganisms can be utilized in the industrial field. The advantages of the application of enzymes in the industrial field, namely the product becomes easily decomposed, requires less energy, and does not produce hazardous waste. One of the potential enzymes in the industrial field is xylanase. Xylanase enzymes can be produced by thermophilic bacteria. The advantage of thermophilic bacteria is that enzymes are more stable and can be stored longer. There is a consortium of bacteria naturally in nature. Consortium has a better ability than pure culture in utilizing the substrate as an energy source. Thermophilic bacteria from Sapan Sungai Aro isolates SSA 2, SSA 3, SSA 4 and SSAS 6 can produce xylanase enzymes. Prior to the consortium, a synergism test was needed to find out if all isolates were synergistic. Furthermore, the synergism test was carried out using the disk diffusion method. The results of the test did not reveal any inhibition zones around the disc paper, so that all SSA 2, SSA 3, SSA 4 and SSAS 6 isolates were synergistic and further tests could be carried out for consortium research.